G438(P) A multi-centre service evaluation of the use of high flow nasal cannula oxygen therapy in the management of infants with bronchiolitis. (May 2019) - Fullwood, I; Aung, W; Holliday, K; Vardon, A; Nuthall, J; Vawda, H; Roked, F; Thapliyal, R
Abstract : Aims: For the management of patients with bronchiolitis, high flow nasal cannula oxygen (HFNCO) therapy is not recommended in national guidelines. Despite this, it is frequently used. We sought out to document how HFNCO therapy is currently being used for patients with bronchiolitis and what the outcomes are for this patient group. Methods: We carried out a retrospective multi-centre service evaluation, with a standardised proforma developed by trainees. Data was collected over a 4 week period, as selected by local data collectors, between 1 st November 2017 and 31 st January 2018. Inclusion criteria were infants<12 months corrected gestational age with a primary diagnosis of bronchiolitis, treated with HFNCO therapy during the escalation phase of management. Results: Data was collected in 7 out of 13 potential hospitals. 78 case notes were reviewed. Median age and weight were 9.3 weeks (range 1.7–50.5), and 4.91 kg (range 2.5–10.88) respectively. There was statistically significant improvement in HR and RR one hour after commencing HFNCO (p=0.033 and 0.003 respectively). Median starting flow rate was 1.99 L/kg (range 1.12–3.84), with maximum flow rates of 4.8 L/kg being used. 36 (50%) patients required escalation of care to at least CPAP. HFNCO was delivered on a paediatric ward for 47 patients (60.3%) and in a HDU bed space for 31 (39.7%) with comparable numbers needing escalation regardless of ward setting; ward 48.6% vs HDU 46.7%. 11 patients (14.5%) required admission to PICU. Feeding practices varied whilst on HFNCO therapy, including NG feeds (24.7%), intravenous (IV) fluids (53.2%) or both (22.1%). If on IV fluids, a third of patients had fluids restricted to <90% of full maintenance. Conclusions: Our real-life data demonstrates wide variability in the use of HFNCO therapy with half of patients going on to need escalation of care. We feel lack of national guidance contributes to this variability in management and more research is needed to determine optimal use, to gain greatest benefit, in a cost-effective way.